2015
DOI: 10.1177/0956797615588467
|View full text |Cite
|
Sign up to set email alerts
|

Neural Affective Mechanisms Predict Market-Level Microlending

Abstract: Humans sometimes share with others whom they may never meet or know, in violation of the dictates of pure self-interest. Research has not established which neuropsychological mechanisms support lending decisions, nor whether their influence extends to markets involving significant financial incentives. In two studies, we found that neural affective mechanisms influence the success of requests for microloans. In a large Internet database of microloan requests (N = 13,500), we found that positive affective featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
130
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(148 citation statements)
references
References 40 publications
14
130
2
2
Order By: Relevance
“…Similarly, Genevsky and Knutson (2015) demonstrated that consumers' affective responses to photographs accompanying microloan requests are an important predictor of market-level microlending decisions. Their research showed that neural imaging data of brain areas involved in affective responses improve prediction accuracy over and above participants' self-reported affective responses -interpreted by WP as evidence for an unconscious effect of affective responses.…”
Section: The Danger In Considering Consciousness Secondmentioning
confidence: 97%
See 3 more Smart Citations
“…Similarly, Genevsky and Knutson (2015) demonstrated that consumers' affective responses to photographs accompanying microloan requests are an important predictor of market-level microlending decisions. Their research showed that neural imaging data of brain areas involved in affective responses improve prediction accuracy over and above participants' self-reported affective responses -interpreted by WP as evidence for an unconscious effect of affective responses.…”
Section: The Danger In Considering Consciousness Secondmentioning
confidence: 97%
“…It could possibly reflect another consciously accessible feature of the photographs that was not measured (e.g., the extent to which they are considered self-relevant). Importantly, neither Genevsky and Knutson (2015) nor Van den Bergh and colleagues (2008) made claims about the (un)conscious nature of the effects they identified.…”
Section: The Danger In Considering Consciousness Secondmentioning
confidence: 98%
See 2 more Smart Citations
“…Neuroimaging investigations of altruistic and prosocial behavior, which may be preferentially linked to care rather than to distress, have linked these behaviors to the mesolimbic dopamine system, including the ventral tegmental area (VTA), ventral striatum (VS), and ventromedial prefrontal cortex (vmPFC) (Harbaugh, Mayr, & Burghart, 2007; Hare, Camerer, Knoepfle, & Rangel, 2010; Moll et al, 2006; Morelli, Sacchet, & Zaki, 2015; Zaki & Mitchell, 2011), especially in the context of positive affect (Genevsky & Knutson, 2015; Genevsky, Västfjäll, Slovic, & Knutson, 2013). In addition, a septal/anterior hypothalamic circuit has been linked to a range of affiliative emotions and behaviors across species, including maternal and juvenile play behavior in rats (Bredewold, Schiavo, van der Hart, Verreij, & Veenema, 2015; Numan, 1988), and in humans, trust (Krueger et al, 2007), charitable donation (Moll et al, 2006), prosocial behavior (Morelli, Rameson, & Lieberman, 2014), support giving (Inagaki & Eisenberger, 2012), and affiliative emotion (Moll et al, 2012, 2014).…”
Section: Introductionmentioning
confidence: 99%